Assessment of dental anxiety and the prevalence of dental caries in a group of 6-9 years old children. - Vlad Ramona; Stoica Oana Elena; Stoica Alexandra Mihaela; Monea Monica ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2020)
Children`s dental anxiety is responsible for increasing dental health problems, as patients avoid seeking treatment. The aim of our study was to evaluate the level of dental anxiety and its correlation with dental health status in a group of children aged between 6-9 years.